2015
DOI: 10.1016/j.tim.2015.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Axonal spread of neuroinvasive viral infections

Abstract: Neuroinvasive viral infections invade the nervous system, often eliciting serious disease and death. Members of four viral families are both neuroinvasive and capable of transmitting progeny virions or virion components within long neuronal extensions known as axons. Axons provide physical structures to spread of viral infection within the host while avoiding extracellular immune responses. Technological advances in analysis of in vivo neural circuits, neuronal culturing, and live imaging of fluorescent fusion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
49
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(54 citation statements)
references
References 72 publications
3
49
1
1
Order By: Relevance
“…In neurotropic viral infections, intra-and interneuronal spread is considered to be a mechanism of immune evasion (51,52). However, our results do not support this assumption for L. monocytogenes.…”
Section: Discussioncontrasting
confidence: 88%
“…In neurotropic viral infections, intra-and interneuronal spread is considered to be a mechanism of immune evasion (51,52). However, our results do not support this assumption for L. monocytogenes.…”
Section: Discussioncontrasting
confidence: 88%
“…Previous authors have shown that US9 is involved in anterograde transport of viral capsids and glycoproteins to axonal termini in related alphaherpesviruses, such as pseudorabies virus (PRV) (58–60). However the role of US9 in anterograde transport of HSV-1 is less clear (61–64).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, 'shingles' as a skin manifestation may reflect subsequent repeated subclinical reactivation of VZV, sometimes in cranial nerves that have a more direct effect on the cerebral arteries [18]. It is possible that the reactivated VZV spreads transaxonally in a centripetal direction like rabies [19], and reaches the cerebral arteries, and this is followed by transmural spread of the virus. Another possible mechanism is that zoster itself or post-herpetic neuralgia increases sympathetic status and adverse emotional reactions, theoretically increasing cerebrovascular risk [20].…”
Section: Discussionmentioning
confidence: 99%